2008
DOI: 10.1027/0269-8803.22.4.157
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Human Race and Face Inversion on the N170

Abstract: To learn whether the N170 would be differentially affected by orientation inversion of same- and other-race faces, we recorded event-related brain potentials (ERPs) in Caucasian and locally resident Asian subjects viewing upright and upside-down front-view photographs of African, Asian, and Caucasian faces. Results show that the time-to-peak was significantly delayed for inverted Caucasian faces in both subject groups. The same-race N170 peaked later than either other-race N170 in the Caucasian, but showed no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
45
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 43 publications
5
45
3
Order By: Relevance
“…N170 amplitudes were similar for the three races of faces when presented in the inverted orientation). More precisely, in line with previous findings (Gajewski et al, 2008;Herrmann et al, 2007;Stahl et al, 2008;Walker et al, Fig. 2.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…N170 amplitudes were similar for the three races of faces when presented in the inverted orientation). More precisely, in line with previous findings (Gajewski et al, 2008;Herrmann et al, 2007;Stahl et al, 2008;Walker et al, Fig. 2.…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, Caldara et al (2004) identified the occurrence of the OR advantage in categorization at around 240 ms, a stage related to the processing of visual information at the semantic level. In addition, some authors found that inversion affects the latency (Gajewski et al, 2008) or the amplitude (Vizioli et al, 2010) of the N170 predominantly for faces from the same race of the participants, while others found that the effects of race and inversion are additive and do not interact (Wiese et al, 2009). Thus, it is yet unclear at the present time whether the ORE is based on differential configural/holistic information processing at the time of the initial face-encoding stage.…”
Section: Introductionmentioning
confidence: 71%
See 2 more Smart Citations
“…Some previous studies have revealed increased N170 amplitudes for other-race than for own-race faces (Caharel et al, 2011;Gajewski, Schlegel, & Stoerig, 2008;Herrmann et al, 2007;Stahl, Wiese, & Schweinberger, 2008;Walker, Silvert, Hewstone, & Nobre, 2007;Wiese, 2012;Wiese, Kaufmann, & Schweinberger, 2014). Since own-race and own-age effects on ERPs are partly comparable (Ebner, He, Fichtenholtz, McCarthy, & Johnson, 2011;Wiese, Schweinberger, & Hansen, 2008), this finding might extend to own-age effects.…”
mentioning
confidence: 66%